2014
DOI: 10.4314/tjpr.v13i9.7
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Screening of &#945;-Amylase Inhibition by Selected Terpenes from Essential Oils

Abstract: Purpose: To assess some terpenes from herbal products for possible inhibitory effects on serum α-amylase in order to ascertain their potential usefulness in the prevention and/or treatment of diabetes Type 2. Methods: Solutions of terpenes (citral, eukalyptol, β-pinene, myrcene, eugenol and terpineol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…4-Terpineol as well as α-pinene, which predominate the essential oil of Fp, were previously reported to possess considerable α-amylase inhibitory activity [24]. Similarly, the potent α-amylase inhibitory potential is mainly due to the synergistic action between the different components, which is in accordance to different previously reported studies that confirmed the α-amylase inhibitory effect of different terpenes and different Ferula species such as F. gummosa essential oil [24,25]. [20].…”
Section: Antioxidant Potential Of Different Ferula Speciessupporting
confidence: 86%
See 1 more Smart Citation
“…4-Terpineol as well as α-pinene, which predominate the essential oil of Fp, were previously reported to possess considerable α-amylase inhibitory activity [24]. Similarly, the potent α-amylase inhibitory potential is mainly due to the synergistic action between the different components, which is in accordance to different previously reported studies that confirmed the α-amylase inhibitory effect of different terpenes and different Ferula species such as F. gummosa essential oil [24,25]. [20].…”
Section: Antioxidant Potential Of Different Ferula Speciessupporting
confidence: 86%
“…Fp and Fv exhibited the most potent α-amylase inhibitory potential as evidenced by their pronounced inhibitory activity, which was equivalent to 2.61 and 1.40 mmol ACAE/g oil, respectively, in which ACAE is the acarbose equivalent, a potent α-amylase inhibitor ( Figure 5). 4-Terpineol as well as α-pinene, which predominate the essential oil of Fp, were previously reported to possess considerable α-amylase inhibitory activity [24]. Similarly, the potent α-amylase inhibitory potential is mainly due to the synergistic action between the different components, which is in accordance to different previously reported studies that confirmed the α-amylase inhibitory effect of different terpenes and different Ferula species such as F. gummosa essential oil [24,25].…”
Section: Antioxidant Potential Of Different Ferula Speciessupporting
confidence: 86%
“…Significant studies based on in vitro screening of α ‐amylase inhibition have revealed the promising activity of the terpenes found in various essential oils . Among the tested compounds are citral, eucalyptol, β ‐pinene, myrcene, eugenol and terpineol.…”
Section: Inhibitory Activity Of Common Terpenoidsmentioning
confidence: 99%
“…Among the tested compounds are citral, eucalyptol, β ‐pinene, myrcene, eugenol and terpineol. In the study, α ‐amylase activity was determined by standard methods using an automated analyzer. Herein, citral exhibited the highest inhibition percentage at lower inhibitor concentrations, while eugenol showed the lowest in the case of ultrasonic preparation of terpenes.…”
Section: Inhibitory Activity Of Common Terpenoidsmentioning
confidence: 99%
“…Other in vitro studies also showed inhibitory properties of eucalyptol against carbohydrate digesting enzymes. 22,23 Despite the multiple pharmacological attributes of eucalyptol, its poor aqueous solubility, chemical instability and high volatility have restricted its oral administration for treatment of various metabolic diseases. When ingested, it is also easily metabolized by liver microsomal enzymes to its hydroxylated derivatives, 2ahydroxy-1,8-cineole and 3a-hxdroxy-1,8-cineole.…”
Section: Introductionmentioning
confidence: 99%